Multifunctional Crosslinking‐Enabled Strain‐Regulating Crystallization for Stable, Efficient α‐FAPbI3‐Based Perovskite Solar Cells. Issue 29 (4th June 2021) - Zhang, Hengkai; Chen, Zhiliang; Qin, Minchao; Ren, Zhiwei; Liu, Kuan; Huang, Jiaming; Shen, Dong; Wu, Zehan; Zhang, Yaokang; Hao, Jianhua; Lee, Chun‐sing; Lu, Xinhui; et al.
Abstract: α‐Formamidinium lead triiodide (α‐FAPbI3 ) represents the state‐of‐the‐art for perovskite solar cells (PSCs) but experiences intrinsic thermally induced tensile strain due to a higher phase‐converting temperature, which is a critical instability factor. An in situ crosslinking‐enabled strain‐regulating crystallization (CSRC) method with trimethylolpropane triacrylate (TMTA) is introduced to precisely regulate the top section of perovskite film where the largest lattice distortion occurs. In CSRC, crosslinking provides in situ perovskite thermal‐expansion confinement and strain regulation during the annealing crystallization process, which is proven to be much more effective than the conventional strain‐compensation (post‐treatment) method. Moreover, CSRC with TMTA successfully achieves multifunctionality simultaneously: the regulation of tensile strain, perovskite defects passivation with an enhanced open‐circuit voltage ( V OC = 50 mV), and enlarged perovskite grain size. The CSRC approach gives significantly enhanced power conversion efficiency (PCE) of 22.39% in α‐FAPbI3 ‐based PSC versus 20.29% in the control case. More importantly, the control PSCs' instability factor—residual tensile strain—is regulated into compression strain in the CSRC perovskite film through TMTA crosslinking, resulting in not only the best PCE but also outstanding device stability in both long‐term storage (over 4000 h with 95% of initial PCE) and light soaking (1248 h with 80% of initial PCE) conditions. Abstract : A universality strain‐regulation approach—crosslinking‐enabled strain‐regulating crystallization (CSRC)—is introduced to eliminate intrinsic tensile strain in perovskite film, which significantly boosts the perovskite solar cells' (PSCs) stability and performance. The CSRC approach precisely modulates the perovskite film strain through synchronous cooperation of perovskite crystallization manipulation and in situ chemical crosslinking process, as showcased with several types of crosslinking agents. ​